Older Than Genes: The Acetyl CoA Pathway and Origins - William F. Martin (Frontiers in Microbiology, 2020)
For decades, microbiologists have viewed the acetyl CoA pathway and organisms that use it for H2-dependent carbon and energy metabolism, acetogens and methanogens, as ancient. Classical evidence and newer evidence indicating the antiquity of the acetyl CoA pathway are summarized here. The acetyl CoA pathway requires approximately 10 enzymes, roughly as many organic cofactors, and more than 500 kDa of combined subunit molecular mass to catalyze the conversion of H2 and CO2 to formate, acetate, and pyruvate in acetogens and methanogens. However, a single hydrothermal vent alloy, awaruite (Ni3Fe), can convert H2 and CO2 to formate, acetate, and pyruvate under mild hydrothermal conditions on its own. The chemical reactions of H2 and CO2 to pyruvate thus have a natural tendency to occur without enzymes, given suitable inorganic catalysts. This suggests that the evolution of the enzymatic acetyl CoA pathway was preceded by—and patterned along—a route of naturally occurring exergonic reactions catalyzed by transition metal minerals that could activate H2 and CO2 by chemisorption. The principle of forward (autotrophic) pathway evolution from preexisting non-enzymatic reactions is generalized to the concept of patterned evolution of pathways. In acetogens, exergonic reduction of CO2 by H2 generates acyl phosphates by highly reactive carbonyl groups undergoing attack by inert inorganic phosphate. In that ancient reaction of biochemical energy conservation, the energy behind formation of the acyl phosphate bond resides in the carbonyl, not in phosphate. The antiquity of the acetyl CoA pathway is usually seen in light of CO2 fixation; its role in primordial energy coupling via acyl phosphates and substrate-level phosphorylation is emphasized here.